Judas Iscariot in the Novel of Roman Brandstaetter "Jesus of Nazareth" - Nalewaj, Aleksandra (Studia Warmińskie, 2019)
The subject of this study is the figure of Judas Iscariot by the novel of Roman Brandstaetter „Jesus of Nazareth”. The author of the literary work – inculcated in the Judaic tradition, brought up in love and respect for inspired writings, knowing the realities of life in Palestine in the first century AC – does not distort the image of Iscariot, known from the Gospel, but extends it. In this way he manages to create a credible psychological portrait of a man who – trusting only himself and his own intuition – falls into an ever-greater sin, until he devotes himself to the services of the Devil.